Exercise and blood flow restriction - Pope, Z. K.; Willardson, J. M.; Schoenfeld, B. J. (The Journal of Strength and Conditioning Research, 2013)
A growing body of research has demonstrated the effectiveness of exercise (low-intensity resistance training, walking, cycling) combined with blood flow restriction (BFR) for increased muscular strength and hypertrophy. The BFR is achieved via the application of external pressure over the proximal portion of the upper or lower extremities. The external pressure applied is sufficient to maintain arterial inflow while occluding venous outflow of blood distal to the occlusion site. With specific reference to low-intensity resistance training, the ability to significantly increase muscle strength and hypertrophy when combined with BFR is different from the traditional paradigm, which suggests that lifting only higher intensity loads increases such characteristics. The purpose of this review was to discuss the relevant literature with regard to the type and magnitude of acute responses and chronic adaptations associated with BFR exercise protocols vs. traditional non-BFR exercise protocols. Furthermore, the mechanisms that stimulate such responses and adaptations will be discussed in the context of neural, endocrine, and metabolic pathways. Finally, recommendations will be discussed for the practitioner in the prescription of exercise with BFR.